An all-fiber laser oscillating directly at a single TE01 mode with ring-core fibers. (3rd April 2019) - Zhang, Yimin; Li, Hongxun; Dai, Chuansheng; Tao, Runxia; Xu, Lixin; Gu, Chun; Chen, Wei; Zhu, Yonggang; Zhan, Qiwen; Yao, Peijun
Abstract: For the first time, an azimuthally polarized fiber laser without any polarization controller is proposed and demonstrated experimentally. The scheme is based on a self-designed ring-core fiber and transverse mode filter (TMF). The ring-core fiber can break the degeneracy of LP11 modes and make the TE01 mode propagate stably in the fiber laser. The TMF, which is made from the ring-core fiber by depositing a layer of aluminum on the cladding surface, can effectively suppress modes other than the TE01 mode. This study opens a new avenue toward the practical application of cylindrical vector beam fiber lasers.